tính
A = \(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
c, Cho x,y,z là các số # 0 và x2 = yz, y2 = xz , z2 = xy. Chứng minh rằng x = y= z
Tính: \(y=\frac{16^3.3^{10}_{ }+120.6^9}{4^6.3^{12}+6^{11}}\)
\(y=\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
\(y=\frac{2^{12}.3^{10}+2^9.3^9.120}{2^{12}.3^{12}+2^{11}.3^{11}}\)
\(y=\frac{2^9.3^9\left(2^3.3+120\right)}{2^{11}.3^{11}\left(2.3+1\right)}\)
\(y=\frac{6^9\left(2^3.3+120\right)}{6^{11}.7}\)
\(y=\frac{2^3.3+120}{6^2.7}\)
\(y=\frac{144}{252}\)
\(y=\frac{4}{7}\)
16^3.3^10+120.6^9/4^6.3^12+6^11
tính
A = \(\dfrac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
c, Cho x,y,z là các số # 0 và x2 = yz, y2 = xz , z2 = xy. Chứng minh rằng x = y= z
tính:\(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
\(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}=\frac{2^{12}.3^{10}+2^3.3.5.2^9.3^9}{2^{12}.3^{12}+3^{11}.2^{11}}=\frac{2^{12}.3^{10}+2^{12}.3^{10}.5}{2^{11}.3^{11}\left(2.3+1\right)}=\frac{2^{12}.3^{10}.\left(1+5\right)}{2^{11}.3^{11}\left(2.3+1\right)}=\frac{2.6}{3.7}=\frac{12}{21}=\frac{4}{7}\)
\(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}=\frac{4}{7}\)
Tính \(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
Lời giải:
Gọi biểu thức là $A$.
\(A=\frac{(2^4)^3.3^{10}+2^3.3.5.2^9.3^9}{2^{12}.3^{12}+2^{11}.3^{11}}\\ =\frac{2^{12}.3^{10}+2^{12}.3^{10}.5}{2^{11}.3^{11}(2.3+1)}\\ =\frac{2^{12}.3^{10}(1+5)}{7.2^{11}.3^{11}}=\frac{2^{12}.3^{10}.2.3}{7.2^{11}.3^{11}}\\ =\frac{2^{13}.3^{11}}{7.2^{11}.3^{11}}=\frac{2^2}{7}=\frac{4}{7}\)
Tính \(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
Tính: A= \(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
Tính
\(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
\(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}=\frac{2^{12}.3^{10}+2^3.3.5.2^9.3^9}{2^{12}.3^{12}+3^{11}.2^{11}}=\frac{2^{12}.3^{10}.\left(1+5\right)}{2^{11}.3^{11}\left(2.3+1\right)}=\frac{2.6}{3.7}=\frac{12}{21}=\frac{4}{7}\)
=\(\frac{2^{13}\cdot3^{10}+2^3\cdot3\cdot5\cdot2^9\cdot3^9}{2^{12}\cdot3^{12}+2^{11}\cdot3^{11}}\)
=\(\frac{2^{12}\cdot3^{10}\cdot\left(1+2\cdot5\right)}{2^{11}\cdot3^{11}\cdot\left(2\cdot3+1\right)}\)
=\(\frac{2\cdot11}{3\cdot7}\)
duyệt nha các bn
=\(\frac{22}{21}\)
Thực hiện phép tính : \(\frac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)